Characterization of plant growth-promoting bacteria from Vicia faba root nodules grown on oasis soils and their potential to enhance soil fertility and crop growth attributes in arid regions - Oumaima Chaieb; Souhir Abdelkrim; Iris Bertani; Wael Taamalli; Khediri Mannai; Fatma Souissi; Moez Jebara; Vittorio Venturi; Salwa Harzalli Jebara (PLoS ONE, 2026)
Soil degradation and nutrient depletion are major constraints in arid regions, particularly in fragile oasis ecosystems. Harnessing beneficial plant-bacteria interactions offers a sustainable approach to improving soil fertility and crop productivity. This study aimed to isolate and characterize plant growth-promoting rhizobacteria (PGPR) from root nodules of V. faba L. var. minor Saber 02 grown on 12 oasis soils, and to evaluate their potential for enhancing plant growth and soil fertility. Sixty bacteria were isolated from V. faba root-nodules. 16S rDNA sequencing revealed seven bacterial orders: Enterobacteriales, Pseudomonodales , Burkholderiales , Xanthomonadales , Rhodospirillales , Hyphomicrobiales , Bacillales . Plant growth promoting (PGP) traits screening identified five of the sixty isolates including Rhizobium laguerreae (Vf19), Bacillus halotolerans (Vf43), Gluconobacter frateurii (Vf47), Pseudomonas reinekei (Vf48), and Kosakonia radicincitans (Vf49) which harbor multiple PGP traits with interesting biocontrol potential as well as high tolerance to osmotic stresses. Eleven inoculums formed by mixing efficient and resistant PGPR to inoculate V. faba L. minor var. Saber 02 in contrasting soil fertility showed that co-inoculation with R. laguerreae Vf19 and B. halotolerans Vf43 significantly increased shoot biomass and nitrogen content. Likewise, inoculation with consortia formed by mixing R. laguerreae Vf19 + B. halotolerans Vf43 and R. laguerreae Vf19 + B. halotolerans Vf43 + K. radicincitans Vf49 improved soil total nitrogen levels by up to 2.5-fold in low-fertility soil. These findings highlight the potential of selected PGPR strains, particularly R. laguerreae Vf19, B. halotolerans Vf43, and K. radicincitans Vf49, as promising candidates for developing effective biofertilizers in management programs for sustainable agriculture in low fertility oasis soils to improve soil health, plant growth and productivity.